The Development of Albanian visual art during XVI – XVIII centuries: Development of Albanian visual art during XVI – XVIII centuries - Zeneli, Fidan (Street Art & Urban Creativity, 2023)
In the second part of the 16th century, Albanian urban society reached a high point of development. Foreign trade flourished to the extent that major Albanian merchants had their agencies in Ragusa, Venice and other medieval urban centers. This prosperity encouraged the development of education and art. Therefore, this paper elaborates some significant features for the Albanian cultural history of the XVI-XVIII centuries. The works of painters and art masters were observed to give a more complete mirror of culture as an integral component of spiritual life, as well as of Albanian history of the XVI-XVIII centuries in general. This paper uses a comprehensive and chronological perspective. This approach with contemporary literature offers us a literal interpretation of cultural or artistic developments from the field of visual art.